PENGARUH LINGKUNGAN BELAJAR DAN KOMPETENSI PROFESIONAL GURU TERHADAP PRESTASI BELAJAR SISWA SMA N 1 JEKULO KUDUS - Rustiana, Ade; Chalifah, Noor (Dinamika Pendidikan, 2012)
Learning environment and teachersâ professional competence are factors which can affect studentsâ achievement. The objective of the study was to determine the influence of learning environment and teachersâ professional competence toward studentsâ achievement either partially or simultaneously. The populations were 133 students and the samples were 100 students. Then, data were collected by questionnaires and documentation. The calculation of multiple regression resulted the equation of Y = 60.866 + 0.114 X1 + 0.048 X2. The coefficient of determination simultaneously; learning environment and teachersâ professional competence toward studentsâ achievement was 53.3%, the coefficient of determination partially; learning environment toward studentsâ achievement was 26.3%, and teachersâ professional competence toward studentsâ achievement was 16.9%. It was concluded that there was significant influence of learning environment toward studentsâ achievement, there was no significant influence of the teachersâ professional competence toward studentsâ achievement, and there was significant influence of learning environment and teachersâ professional competence toward studentsâ achievement.